Stereoselective Synthesis of Benzosultam-Fused Tetrahydroquinazolines via [4+2]-Cycloaddition of Cyclic N-Sulfonyl Ketimines with 2-Aminophenyl Enones - Han, Ji Won; Kim, Sung-Gon (Synthesis, 2025)
A [4+2]-cycloaddition reaction between cyclic N-sulfonyl ketimines and 2-aminophenyl enones, catalyzed by K2CO3, has been developed. This method provides a straightforward and efficient approach for synthesizing a wide range of structurally complex and highly functionalized benzosultam-fused tetrahydroquinazolines in high yields, with excellent diastereoselectivities.
Keywords: [4+2]-cycloaddition; benzosultams; 2-aminophenyl enones; cyclic N-sulfonyl ketimines; tetrahydroquinazolines